If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = -9 + y Solving 0 = -9 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 0 + -1y = -9 + y + -1y Remove the zero: -1y = -9 + y + -1y Combine like terms: y + -1y = 0 -1y = -9 + 0 -1y = -9 Divide each side by '-1'. y = 9 Simplifying y = 9
| 8x=90+x | | 12+k-2=5k-2k | | 10-(x-4)=45 | | -5(-8m+1)=-5+3m | | 7x+3-6x=8-30 | | -2=-9+y | | -7-x= | | 12x-96=0 | | (10X+6)-(5X+4)= | | (90-x)=5(180-x)-10 | | c-7=9 | | .5(8n-14)= | | 3(x+2)+6=36 | | 14-2z=16 | | 8p-(6pg+4p)= | | -4=-9+y | | log(7x+3)=4 | | 100a+100a= | | 4(2/3h-3)= | | 21x^2-32x-5=0 | | 12x+14= | | 2j-6=3j | | 9x-3y=-2 | | 5x-2(x+3)=7(x+2) | | 8(x^2+16)=9 | | 10(15-6z)= | | 3+8n=6n-1 | | 3(3y-9)=2(y-3) | | (90-x)=1/5(180-x)-10 | | 5ab+3a^2b-0.5ab= | | 50=-2(24-x)+4(x-4) | | -3n+1=-4n+8 |